Laying Waste in Archaeological Sites. The Problems of Damage to Historical Sacred Objects as a Result of Human Activity - Dawid Grupa (Fasciculi Archaeologiae Historicae, 2019)
Excavation works conducted in archaeological sites deliver a great deal of information concerning the material and spiritual culture of past populations. In many instances, for example in settlements and towns, researchers find all kinds of rubbish dumps connected with everyday human activity, which are a rich cognitive source for archaeologists. However, in many cases, before reaching cultural layers, archaeologists have to dig through recent layers disrupting the cognitive value of a site. Cult places, which have an important spiritual role in the life of local societies, like spaces serving for centuries as cemeteries should be exceptions from that rule, but rarely are so. All archaeological explorations conducted in crypts start with clearing work to remove rubbish deposited inside. Depending on easy access to crypts situated beneath church floors, the rubbish includes objects intentionally deposited there by people or collected by wild animals having taken shelter there. Every intrusion affects the microclimate of the interior; collected rubbish also has a destructive character, leading to decay processes. Intensive micro-organic development and internal damp also affects the condition of the church walls standing above the crypt.